1997
DOI: 10.1007/bf02495334
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of capillary zone electrophoresis and micellar electrokinetic chromatography for the separation of twelve aromatic sulphonate compounds

Abstract: SummaryTwo modes of capillary electrophoresis (CE), capillary zone electrophoresis (CZE) and micellar electrokinetic chromatography (MEKC), were investigated for the separation of 12 aromatic sulphonate compounds. In CZE, although the voltage applied, the buffer concentration and the pH were optimized for effective separation of the compounds studied, under the best conditions four of the five amino compounds coeluted, as did naphthalene-l-sulphonic acid and naphthalene-2-sulphonic acid. In MEKC, sodium dodecy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Although it has previously been shown that micellar electrokinetic chromatography (MEKC) gives better results than capillary zone electrophoresis (CZE) for sulphonated aromatic compounds [21], consistent results could not be obtained by use of MEKC with the five sulphonated anthraquinones under investigation in this work. Indeed, neither the reproducibility of the peak migration times nor peak shapes was satisfactory (results not shown).…”
Section: Resultsmentioning
confidence: 59%
“…Although it has previously been shown that micellar electrokinetic chromatography (MEKC) gives better results than capillary zone electrophoresis (CZE) for sulphonated aromatic compounds [21], consistent results could not be obtained by use of MEKC with the five sulphonated anthraquinones under investigation in this work. Indeed, neither the reproducibility of the peak migration times nor peak shapes was satisfactory (results not shown).…”
Section: Resultsmentioning
confidence: 59%
“…The analysis time is considerably shorter when coelectroosmotic CZE (Figure 2b) is used instead of counterelectroosmotic CZE [7]. The analysis time varies from 6 rain for coelectroosmotic CZE to 14 min for counterelectroosmotic CZE.…”
Section: Hdb Systemmentioning
confidence: 98%
“…Stock aqueous solutions of CTAB and HDB were prepared weekly at 20 mM and 0.5 % (w/v) respectively. All buffer solutions were 20 mM sodium tetraborate, pH 8.7 [7] and the appropriate amounts of CTAB or HDB and organic solvent. Before use, buffer solutions were sonicated and filtered through a 45-pro nylon syringe-filter (Corning, USA).…”
Section: -Ns) and (12) 5-amino-2-naphthalenesulphonic Acid (5-nh2-2-mentioning
confidence: 99%
See 1 more Smart Citation
“…Since initial work by Terabe and coworkers [I, 2], MEKC has developed into a routine separation technique for improving separation efficiency not only for uncharged compounds but also for many ionic compounds. Some ionic analytes not successfully separated by capillary zone electrophoresis (CZE) can be separated by MEKC [3,4].…”
Section: Introductionmentioning
confidence: 99%